2006
DOI: 10.1111/j.1439-0434.2006.01098.x
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate and Previous Crop Residue Effect on Deleterious and Beneficial Soil‐borne Fungi from a Peanut–Corn–Soybean Rotations

Abstract: Bean seedlings (Phaseolus vulgaris L.) were transplanted to soil with corn previous crop residue, peanut previous crop residue and no agricultural soil, and treated with a range of glyphosate concentrations. Trichoderma, Gliocladium, Fusarium and Pythium soil-borne fungi populations were monitored during 24 days after glyphosate treatment to study the glyphosate and previous crop residue effects on these populations. In addition, those genera of soil-borne fungi were tested to study in vitro toxicity to glypho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 25 publications
1
22
1
1
Order By: Relevance
“…abundance and diversity, soil microbial respiration, biomass or activity. Several studies (Doran 1980;Gupta and Germida 1988;Vargas Gil et al 2008) stress that, unlike monoculture, crop rotation can stimulate soil biodiversity and biological activity through changes in the soil habitat, favouring the development of specific microbial communities (Meriles et al 2006). Accordingly, because of the different quality and amount of exudates and organic components from root systems and crop residues, some groups of microorganisms can be differently influenced by crop sequence, supporting the diverse results obtained in this work.…”
Section: Crop Rotationsupporting
confidence: 69%
“…abundance and diversity, soil microbial respiration, biomass or activity. Several studies (Doran 1980;Gupta and Germida 1988;Vargas Gil et al 2008) stress that, unlike monoculture, crop rotation can stimulate soil biodiversity and biological activity through changes in the soil habitat, favouring the development of specific microbial communities (Meriles et al 2006). Accordingly, because of the different quality and amount of exudates and organic components from root systems and crop residues, some groups of microorganisms can be differently influenced by crop sequence, supporting the diverse results obtained in this work.…”
Section: Crop Rotationsupporting
confidence: 69%
“…Means et al (2007) detected a signiûcant increase in soil Fusarium within two weeks after glyphosate was applied at recommended rates in the ûeld. Meriles et al (2006) verified that the population growth and sporulation of soil Fusarium spp. increased after glyphosate application to soils containing maize or peanut crop residues compared with lower Fusarium populations in similar fallowed soils lacking crop residues.…”
Section: Poe Glyphosate On Growth Yield and Quality Of Maizementioning
confidence: 98%
“…This effect was larger in soils that had greater previous exposure to glyphosate. Other studies have shown that glyphosate use is associated with an increase in the plant pathogens Fusarium and Pythium [42]. Glyphosate can stimulate the growth of mycorrhizal fungi in vitro.…”
Section: Fig 2-gc-ms Analysis and Mass Spectrum Of Glyphosate; Zero mentioning
confidence: 99%